Interaction in online classes during Covid-19: the experiences of newly-arrived migrant students. Issue 3 (3rd July 2022) - Seynhaeve, Shauny; Deygers, Bart; Simon, Ellen; Delarue, Steven
ABSTRACT: Background: In order to continue educational provision during the Covid-19 pandemic, many education systems switched to some form of Emergency Remote Teaching (ERT) in 2020. Research suggests that this may have disproportionately affected students from underprivileged communities. In this context, there is, therefore, a pressing need to consider how ERT may have impacted learners who are likely to be most affected by educational inequalities, including newly arrived migrant students (NAMS). Purpose: As studies have highlighted the particular importance of interaction for effective distance learning, the research aimed to examine how NAMS in Flemish secondary schools experienced interaction with learning content, teachers and fellow students in online classes during ERT. Methods: A total of six semi-structured focus group interviews were conducted with 23 NAMS from six secondary schools in Belgium. The interviews were centred on questions about participants' experiences with online interaction and participation. All focus groups were audio recorded and transcribed verbatim, after which transcriptions were coded and analysed qualitatively. Findings: The analysis revealed that, during ERT, participants reported experiencing a higher amount of learner–content interaction, mainly consisting of self-study material and tasks. Participants also indicated a lack of learner–teacher interaction, which was attributed to the shortage of speaking opportunities and students' decreased inclination to interact with instructors. In addition, most participants reportedly experienced few opportunities for learner–learner interaction during online classes. Conclusions: Study findings provided insight into the NAMS' experiences of being suddenly and unexpectedly compelled to be autonomous learners during ERT. Students' reports suggest that the quality of learner–content interaction may have been compromised by limited learner–teacher interaction in the ERT situation. This draws attention more generally to the importance of interactive learning in the support of NAMS and the need for educators to be empowered to develop interactivity-rich remote learning environments.